Representasi Budaya pada Novel Arah Langkah Karya Fiersa Besari: Kajian Semiotika Roland Barthes - Cahya Farida Putri; Ahmad Ilzamul Hikam (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to describe and analyze the representation of Indonesian culture in Fiersa Besari's novel Arah Langkah using Roland Barthes' semiotic approach. This novel presents the narrative of the journey of the novel's characters who discover the diversity of Indonesian culture through geographical descriptions, customs, and social interactions that occur. Using descriptive qualitative methods and literature studies, the study examines the cultural signs that appear in the text in depth at the level of denotative, connotative, and cultural myth meanings. Barthes' approach allows the disclosure of layers of symbolic and ideological meanings hidden in the novel's cultural representation. The results of the analysis are expected to enrich literary and cultural studies, increase readers' appreciation of Indonesian cultural values, and contribute to the preservation of the nation's cultural identity amidst the flow of globalization. This study also emphasizes the role of the novel as a medium for reflecting socio-cultural life and a means of learning life values through the experiences of characters in the story.